Heterogeneous effects of audit firm characteristics on readability of key audit matters (KAM): evidence from panel quantile regression / Norazian Hussin ... [et al.] - Hussin, Norazian; Md. Salleh, Mohd Fairuz; Ahmad, Azlina; Rahmat, Mohd Mohid (UiTM Press, 2024)
The readability of KAM has been a major concern for academics; given the increasing complexity of financial reporting, the language used to explain KAM may be challenging to articulate effectively. Thus, this study was motivated to offer empirical insights into the heterogeneous effect of audit firm characteristics on KAM readability. Using the Flesch reading ease index to proxy KAM readability, this study utilised 258 FTSE100 Malaysia-listed companies from 2017 to 2019 and used the panel quantile with fixed effects regression analysis. The results showed that Big 4 audit firms, audit fees, busy season, audit firm tenure, and female partners had a significant and heterogeneous effect on the readability of KAM across low (25th), medium (50th), and upper (75th) quantile levels. However, the highest quantile (90th) demonstrated that only audit fees, busy season, and female audit partners significantly affected the conditional distribution of KAM readability. The current study also identified a heterogeneous impact of the audit committee’s characteristics on the readability of KAM in Malaysia.